Controle genético da resistência parcial, adaptabilidade e estabilidade frente à ferrugem asiática da soja - Martins, Juliana Araújo Santos (2011)
The main objectives of this study were to obtain information about the genetic control of the inheritance of partial resistance to Asian rust in soybean lines and to assess the adaptability and phenotypic stability of soybean lines for partial resistance. In order to study the genetic control of partial resistance rust severity was evaluated on individual plants (parents and segregating generations) derived from the crosses Caiapônia x IAC 100 and Luziânia x Potenza. The average genetic components of variance were evaluated employing the weighted least squares method. It was also estimated the number of genes and the broad and narrow sense heritability. The adaptability and phenotypic stability of strains were evaluated in both 2007/08 and 2008/09 seasons in two trials, according to their maturation cycle (early and middle/late), using the rust severity as a trait to select for partial resistance. The advanced lines were evaluated in the locations of Uberlândia and Uberaba in MG State, Campo Alegre de Goiás and Senador Canedo in Goiás State. The severity of the rust was obtained by visual assessment of the leaflets and so it was estimated the average of absolute rate of the disease progress (r), area under the disease progress curve (AUDPC) and partial resistance factor (PRF). Adaptability and stability of the strains were estimated by the methods proposed by Annicchiarico, Eberhart and Russell, as well as by the AMMI method. In the study of the genetic control of rust resistance it was concluded that the character is controlled by 2 to 23 genes, with predominantly dominant effects. The estimate of narrow sense heritability was above 70% for Caiapônia x 100 IAC and wide sense over 60% for Luziânia x Potenza, showing good possibility of success for early generation selection of resistant individuals. Considering the adaptability and stability of resistance, it was found that the strains that were the most resistant to rust, in general, also showed the best adaptability and stability, especially: UFU 001 ((Liderança x UFV 16) x (UFU18 x Br 95015308)), UFU 006 (Canário x Conquista), UFU 007(RC1 PI 416937 x IAC 8.2), UFU 009 (RC2 (IAC 100 x Emgopa 302)) and UFU 0013 ((FT 45.302 x Liderança) x (FT 4.2988 x MG-BR 46 Conquista)), all of early cycle, and those of medium and late cycle: UFU 106 ((DM Vitória x FT 104) x (FT 107 x Liderança)), UFU 110 ((IAS 5 x Br 4) x UFV 16)) and UFU 114 (FT 50268M x UFV 18). The methods used allowed to identify soybean lines more stable and responsive as far as partial resistance was concerned.